The economics of minority voter supression in the United States : A difference-in-difference econometric analysis on the effects of voter ID legislation on minority turn-out in congressional elections - Varumo, Juho (My University, 2020)
The topic of voter ID laws in the United States of America has been a hotly debated one. In the first two decades of the 21st century, the number of states that have some form of voter ID law in effect has gone from 14 to 34. There has been a particular concern that voter ID laws may have disproportionate negative effects on racial and ethnic minorities. Voter ID laws are perceived as part of a long history of minority voter suppression that has roots from since before the Civil War, and continues to this day. This thesis uses econometric analysis to answer the question of whether or not racial and ethnic minorities, specifically Black and Hispanic voters, are disproportionately affected by voter ID laws, compared to White voters. It uses data from the U.S. Census Bureau’s Current Population Surveys for midterm elections from 1998 to 2018. Previous studies have found that there is reason to believe that voter ID laws are politically motivated and intended to suppress Democratic turnout. Studies show that Black and Hispanic voters are less likely to have the voter ID documents needed to vote. However, studies have, with few exceptions, found little evidence that voter ID laws decrease voter turnout for Black or Hispanic voters. Difference-in-difference studies have also found little evidence that Hispanic and Black voter turnout is affected more or less by ID laws than White turnout. The result of the econometric analysis is that the data does not support the view that voter ID laws decrease voter turnout for Black or Hispanic voters. The difference-in-difference analysis comparing the effects of voter ID laws on the change in Black and Hispanic voter turnout to the change in White voter turnout does not show a difference in these changes either. Overall, no evidence is found to support that Black or Hispanic voter turnout suffers from ID laws, or that Black or Hispanic voter turnout suffers disproportionately compared to White voters.

Yhdysvalloissa äänestäjien henkilöllisyystodistuslait ovat kiistelty puheenaihe. 2000-luvun kahdella ensimmäisellä vuosikymmenellä henkilöllisyystodistuslakien määrä on noussut 14:sta 34:ään. Erityisenä huolenaiheena on ollut se, että henkilöllisyystodistuslakien vaikutus voi olla suhteettoman suuri rotuvähemmistöille ja etnisille vähemmistöille. Henkilöllisyystodistuslait ovat osa pitkää vähemmistöjen äänestysoikeuksien rajoittamisen historiaa, joka on jatkunut ajasta ennen sisällissotaa nykypäivään saakka. Tämä tutkielma käyttää menetelmänään ekonometrista analyysiä vastatakseen kysymykseen, vaikuttavatko henkilöllisyystodistuslait mustien ja latinoamerikkalaisten äänestysaktiivisuuteen enemmän kuin valkoisten. Lähteenään tutkielma käyttää U.S. Census Bureaun Current Population Survey -tutkimuksia vuosien 1998–2018 välivaaleista. Aikaisemmissa tutkimuksissa on löydetty viitteitä siihen, että henkilöllisyystodistuslaeilla on tavoiteltu poliittisia päämääriä, ja niiden säätämisellä on ollut tarkoitus vaikuttaa demokraattisen puolueen kannattajien äänestysmahdollisuuksiin. Tutkimuksissa on todettu, että mustilla ja latinoamerikkalaisilla äänestäjillä on pienemmällä todennäköisyydellä lain vaatima äänestämiseen vaadittava henkilöllisyystodistus. Tästä huolimatta tutkimukset ovat harvoja poikkeuksia lukuun ottamatta todenneet, että henkilöllisyystodistuslait eivät vähennä mustien tai latinoamerikkalaisten äänestysaktiivisuutta. Difference-in-difference-analyysiä hyödyntäneet tutkimukset eivät myöskään ole havainneet henkilöllisyystodistuslakien vaikuttavan mustien ja latinoamerikkalaisten äänestysaktivisuuden muutokseen enemmän tai vähemmän kuin valkoisten äänestysaktiivisuuteen. Tutkielman ekonometrinen analyysi päätyy tulokseen, että data ei tue väitettä, että henkilöllisyystodistuslait vähentäisivät mustien tai latinoamerikkalaisten äänestäjien äänestysaktiivisuutta. Difference-in-difference-analyysi ei myöskään tue väitettä, että henkilöllisyystodistusten aiheuttama muutos mustien ja latinoamerikkalaisten äänestysaktiivisuudessa olisi erisuuruinen kuin muutos valkoisten äänestysaktiivisuudessa.
Keywords: Voter ID laws, voting rights, race, ethnicity